Introduction to policing - Scaramella, Gene L.; Cox, Steven M.; McCamey, William (Thousand Oaks, Calif. : SAGE Publications, 2011)
Synopsis: Focusing on the thought-provoking, contemporary issues that underscore the challenging world of policing, this easy-to-understand text balances theory, research, and practice to give students a comprehensive overview of both the foundations of policing and the expanded role of today's police officers. The engaging writing style and stories from the field, coupled with unique coverage of the issues of policing in multicultural communities the impact of globalization on policing, make this book a must have for policing courses. Key features: Around the world sections provide an international perspective on policing issues to prepare readers to think and plan globally in today's interconnected world. You decide features present realistic policing dilemmas and ask students to propose possible solutions. Case in point features use current news articles to illustrate one or more of each chapter's major issues. Police stories features use first-person vignettes, drawn from the authors' previous law enforcement experiences, to bring policing dilemmas to life. Chapter-ending study aids include learning objectives, key terms, key points, 8 to 10 discussion questions based on the learning objectives, 3 to 5 web exercises, and links to scholarly articles. A comprehensive online ancillary package includes a password-protected instructor teaching site and an open-access Student Study Site. Student Study Site with self-quizzes, journal articles, and links to online videos and audio programming, among other learning enhancements.
15: Future Of Policing In The United States -- Chapter learning objectives -- Changing police role -- Research and planning as police functions -- Changing the police image -- Community and problem oriented policing -- Civilianization -- Accreditation -- Lateral entry -- Training -- Education -- Police leadership -- Private and contract security personnel -- Technological changes in policing -- Clarifying the police role -- Predictive policing -- Role of community policing -- Intelligence-led policing and terrorism -- Terrorism laws -- Chapter summary -- Key terms -- Discussion questions -- Internet exercises -- Glossary -- References -- Photo credits -- Index -- About the authors.
Completely reorganized and updated version of: Contemporary municipal policing / William P. McCamey, Gene L. Scaramella, Steven M. Cox. c2003.
Includes bibliographical references and index.
Keywords: Police -- United States; Community policing -- United States